Fundamental Contribution and Host Range Determination of ANP32A and ANP32B in Influenza A Virus Polymerase Activity - Zhang, Haili (J Virol, 2019)
The polymerase of the influenza virus is part of the key machinery necessary for viral replication. However, the avian influenza virus polymerase is restricted in mammalian cells. The cellular protein ANP32A has been recently found to interact with viral polymerase and to influence both polymerase activity and interspecies restriction. We report here that either human ANP32A or ANP32B is indispensable for human influenza A virus RNA replication. The contribution of huANP32B is equal to that of huANP32A, and together they play a fundamental role in the activity of human influenza A virus polymerase, while neither human ANP32A nor ANP32B supports the activity of avian viral polymerase. Interestingly, we found that avian ANP32B was naturally inactive, leaving avian ANP32A alone to support viral replication. Two amino acid mutations at sites 129 to 130 in chicken ANP32B lead to the loss of support of viral replication and weak interaction with the viral polymerase complex, and these amino acids are also crucial in the maintenance of viral polymerase activity in other ANP32 proteins. Our findings strongly support ANP32A and ANP32B as key factors for both virus replication and adaptation. IMPORTANCE The key host factors involved in the influenza A viral polymerase activity and RNA replication remain largely unknown. We provide evidence here that ANP32A and ANP32B from different species are powerful factors in the maintenance of viral polymerase activity. Human ANP32A and ANP32B contribute equally to support human influenza viral RNA replication. However, unlike avian ANP32A, the avian ANP32B is evolutionarily nonfunctional in supporting viral replication because of a mutation at sites 129 and 130. These sites play an important role in ANP32A/ANP32B and viral polymerase interaction and therefore determine viral replication, suggesting a novel interface as a potential target for the development of anti-influenza strategies.